Estimating uncertainty in limit state capacities for reinforced concrete frame structures through pushover analysis - Yu, Xiaohui (2016)
In seismic fragility and risk analysis, the definition of structural limit state (LS) capacities is of crucial importance. Traditionally, LS capacities are defined according to design code provisions or using deterministic pushover analysis without considering the inherent randomness of structural parameters. To assess the effects of structural randomness on LS capacities, ten structural parameters that include material strengths and gravity loads are considered as random variables, and a probabilistic pushover method based on a correlation-controlled Latin hypercube sampling technique is used to estimate the uncertainties in LS capacities for four typical reinforced concrete frame buildings. A series of ten LSs are identified from the pushover curves based on the design-code-given thresholds and the available damage-controlled criteria. The obtained LS capacities are further represented by a lognormal model with the median mc and the dispersion βc. The results show that structural uncertainties have limited influence on mc for the LSs other than that near collapse. The commonly used assumption of βc between 0.25 and 0.30 overestimates the uncertainties in LS capacities for each individual building, but they are suitable for a building group with moderate damages. A low uncertainty as βc=0.1~0.15 is adequate for the LSs associated with slight damages of structures, while a large uncertainty as βc=0.40~0.45 is suggested for the LSs near collapse.